2000
DOI: 10.1002/1097-4547(20000915)61:6<701::aid-jnr14>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Efflux of osmolyte amino acids during isovolumic regulation in hippocampal slices

Abstract: The efflux of potassium (K(+)) and amino acids from hippocampal slices was measured after sudden exposure to 10% (270 mOsm), 25% (225 mOsm) or 50% (150 mOsm) hyposmotic solutions or after gradual decrease (-2.5 mOsm/min) in external osmolarity. In slices suddenly exposed to 50% hyposmotic solutions, swelling was followed by partial (74%) cell volume recovery, suggesting regulatory volume decrease (RVD). With gradual hyposmotic changes, no increase in cell water content was observed even when the solution at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
(45 reference statements)
1
10
1
Order By: Relevance
“…The glycine‐evoked GABA release studied here was largely prevented by niflumic acid and NPPB, inhibitors of anion channels. Efflux through anion channels was described in the case of anionic compounds, particularly glutamate (Franco et al, ; Raiteri et al, ; Milanese et al, ), but also in experiments with the zwitterion GABA (Lee et al, ; Peng et al, ). In recent work (Romei et al, ) it was found that GABA uptake into cerebellum nerve endings was able to stimulate release of the zwitterion glycine essentially by permeation through anion channels.…”
Section: Discussionmentioning
confidence: 95%
“…The glycine‐evoked GABA release studied here was largely prevented by niflumic acid and NPPB, inhibitors of anion channels. Efflux through anion channels was described in the case of anionic compounds, particularly glutamate (Franco et al, ; Raiteri et al, ; Milanese et al, ), but also in experiments with the zwitterion GABA (Lee et al, ; Peng et al, ). In recent work (Romei et al, ) it was found that GABA uptake into cerebellum nerve endings was able to stimulate release of the zwitterion glycine essentially by permeation through anion channels.…”
Section: Discussionmentioning
confidence: 95%
“…Molecules involved and mechanisms in operation are not known in detail, as studies on isovolumetric regulation (IVR) are still scarce. Occurrence of IVR has been found in only two types of renal cells (47,49), in hippocampal slices (50) (fig. 3), and with lower efficiency in C6 glioma cells (51) and in cardiomyocytes (52).…”
Section: Isovolumetric Regulationmentioning
confidence: 99%
“…In A6 cells and in myocytes, IVR stimulates K + release, but only at delayed phase of IVR, with an efflux threshold at -30% hyposmotic external osmolarity. In contrast, amino acids, particularly taurine, appear involved at earlier phases of volume regulation, showing efflux thresholds at approximately -10 to 12% hyposmolarity (50) (fig. 3).…”
Section: Isovolumetric Regulationmentioning
confidence: 99%
“…; Franco et al . ). Observations on the preferential release of taurine from glia, and findings that in taurine‐depleted cells cell volume regulation is impaired, lead to the suggestion that this atypical amino acid serves as a major regulatory osmolyte, and that its release is regulated via a distinct mechanism (Moran et al .…”
Section: Discussionmentioning
confidence: 97%